If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4 + 8x = -4 Reorder the terms: -4 + 6x + 8x = -4 Combine like terms: 6x + 8x = 14x -4 + 14x = -4 Add '4' to each side of the equation. -4 + 4 + 14x = -4 + 4 Combine like terms: -4 + 4 = 0 0 + 14x = -4 + 4 14x = -4 + 4 Combine like terms: -4 + 4 = 0 14x = 0 Solving 14x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '14'. x = 0 Simplifying x = 0
| (125*x-108)/(14*x-15) | | .25/.5=m/8 | | (4+i)-(2+3i)=0 | | 5x^2*6x^2= | | x-38=18-6x | | x+60*0+1=1 | | 9x+4(x+9)= | | 2/3•t=9 | | x+60*0+1=11 | | -2b-6+b-2= | | 2xy*x= | | x+60*0+1=61 | | 60+60*0+x=61 | | X=(2-3k)y | | 17/50=x/25 | | 0.04(y-6)+0.10y=0.12y-0.01(20) | | 9-17r=6 | | 60+x*0+1=61 | | 16o?8=56 | | (1+r)-(1+g)=9 | | 6(x-1)=3(x-5) | | 2100/6 | | 28-2x=18 | | F(2)+1=3(2)+1+2 | | D/5=-22 | | W/4=1.2 | | 3a-39ab= | | 2-i/9-7i | | 6+e/3=5 | | 5(k-2)-3(k-6)=0 | | .4/m=2/4.5 | | 7x+49=175 |